P-34 Dying on the streets: palliative care for people who are homeless or vulnerably housed. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Flemming, Kate; Skelton, Alison; Ruddock, Lynda; Russell, Michael; Chidlow, Helen; Johnson, Emma
Abstract : Background: People who are homeless or vulnerably housed are likely to die young, with an average age of death of 45 years. Many experience life-limiting illnesses, further complicated by dependence on alcohol or drugs. These illnesses can cause significant problems in the last year of life, however, access to palliative care is severely limited. Aim: To develop a co-ordinated approach to palliative and end of life care for people who are homeless and vulnerably housed across the city of York. Approach: The project began with research undertaken at the University of York (Hudson, Flemming, Shulman & et al ., 2016; Skelton, 2017) informing education in end of life care for Changing Lives hostel staff, delivered by St Leonard's Hospice. The education programme had a positive impact on care, however, joint working across organisations highlighted that vulnerable individuals were falling through 'gaps' in end of life care provision. This was the catalyst to bring together health professionals working with the homeless population of York and palliative care specialists to develop: processes of identification of individuals nearing the end of life, guidelines for symptom management, advance care planning and palliative care education. Next steps: Drawing on best practice nationally, we aim to develop a responsive service relevant to the needs of service users at the end of life.